Criminalisation of misappropriation of Traditional Cultural Expression (TCE) - Ismail, Suzi Fadhilah; Abdul Ghani Azmi, Ida Madieha (UPM Press, 2015)
An act can only be regarded as a crime if its exercise can cause harm to others. On that basis, many activities that usurp copyright and can possibly pose harm to the society have been criminalised. In relation to traditional cultural expression, model laws such as the World Intellectual Property Organisation (WIPO) Draft Articles on the Protection of Traditional Cultural Expressions (2011), WIPO-UNESCO (the United Nations Educational, Scientific and Cultural Organisation) Model Provisions for National Laws on the Protection of Expression of Folklore Against Illicit Exploitation and Other Prejudicial Action (1982) and the South Pacific Model Law for National Laws (2002), as well as some national laws of the United States of America and the Philippines have criminalised certain acts constituting the misappropriation of traditional cultural expressions (TCEs). TCEs or expressions of ‘folklore’ are considered by many developing countries as part and parcel of their cultural fabrics and their misappropriation as ‘harmful’ not only to the right holder’s interest but also to the country. To that extent, the misappropriation of TCEs must be criminalised. This paper commences with an examination of copyright protection over TCEs in Malaysia with a view to assessing the adequacy, relevancy and efficacy of criminal sanction and ensuring effective enforcement against misappropriation of indigenous TCEs. The article also examines national initiatives on TCEs, particularly countries that have criminal provisions on certain activities involving TCEs. To lend support for criminalisation, the article further revisits the initiatives of WIPO and UNESCO. The article concludes that introducing some form of criminal offences within the context of copyright law is possible either through the extension of the existing criminal provisions or by having a special part dealing only with misappropriation of TCEs.